Optimisation of xylanases production by two Cellulomonas strains and their use for biomass deconstruction - Ontañon, Ornella Mailen (2021)
One of the main distinguishing features of bacteria belonging to the Cellulomonas genus is their ability to secrete multiple polysaccharide degrading enzymes. However, their application in biomass deconstruction still constitutes a challenge. We addressed the optimisation of the xylanolytic activities in extracellular enzymatic extracts of Cellulomonas sp. B6 and Cellulomonas fimi B-402 for their subsequent application in lignocellulosic biomass hydrolysis by culture in several substrates. As demonstrated by secretomic profiling, wheat bran and waste paper resulted to be suitable inducers for the secretion of xylanases of Cellulomonas sp. B6 and C. fimi B-402, respectively. Both strains showed high xylanolytic activity in culture supernatant although Cellulomonas sp. B6 was the most efficient xylanolytic strain. Upscaling from flasks to fermentation in a bench scale bioreactor resulted in equivalent production of extracellular xylanolytic enzymatic extracts and freeze drying was a successful method for concentration and conservation of the extracellular enzymes, retaining 80% activity. Moreover, enzymatic cocktails composed of combined extra and intracellular extracts effectively hydrolysed the hemicellulose fraction of extruded barley straw into xylose and xylooligosaccharides.